Knowledge work in aircraft maintenance - Sobbe, Eileen [Verfasser]; Tenberg, Ralf [Verfasser]; Mayer, Hans-Georg [Verfasser] (My University, 2016)
"Knowledge work encompasses information processing and knowledge development tasks and places the knowledge worker at the centre of analysis. Knowledge and information are the knowledge worker's most precious resource in an increasingly complex working environment. Knowledge work is analysed in the context of the productive technical working environment of aircraft maintenance at Lufthansa Technik AG. The proportion of knowledge-intensive tasks in aircraft maintenance rises with increasing complexity of aircraft and their systems and components. The quantity of information and the resulting challenges for workers also increase accordingly. The findings generated by the study and a theoretical consideration of the subject are used to derive conclusions about the practice of aircraft maintenance and concrete recommendations for action." (author's abstract, BIBB-Doku)

"Wissensarbeit umfasst Tätigkeiten der Informationsverarbeitung und Entwicklung von Wissen und stellt dabei den Wissensarbeiter in den Mittelpunkt der Betrachtung. Für ihn sind Wissen und Information die kostbarste Ressource in einem zunehmend komplexer werdenden Arbeitsumfeld. Wissensarbeit wird innerhalb des produktiven technischen Arbeitsumfeldes der Flugzeugwartung der Lufthansa Technik AG analysiert. Der Anteil wissensintensiver Tätigkeiten in der Flugzeugwartung steigt mit zunehmender Komplexität der Fluggeräte, deren Systeme und Komponenten. Die Informationsmenge und die sich daraus ergebenden Anforderungen an die Mitarbeiter nehmen entsprechend zu. Anhand der gewonnenen Erkenntnisse der Studie sowie der theoretischen Betrachtung der Thematik werden Konsequenzen für die Praxis der Flugzeugwartung abgeleitet und konkrete Handlungsempfehlungen gegeben." (Autorenreferat, BIBB-Doku)
Wissensarbeit in der Flugzeugwartung
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; S 5.2 Wissensmanagement; G 1.2.4.1.4 Verarbeitendes Gewerbe; Wissensarbeit; Flugzeugindustrie; Wissen; Information; Qualifikationsanforderung